2019
DOI: 10.1111/jan.14226
|View full text |Cite
|
Sign up to set email alerts
|

Academic self‐efficacy in Bachelor‐level nursing students: Development and validation of a new instrument

Abstract: Aims: An available strategy to counteract academic failure is the development and implementation of student academic self-efficacy; however, to date, there are no instruments measuring it. The aim of this study was to develop and psychometrically test an academic nurse self-efficacy scale. Design: A longitudinal study design was used in accordance with Consensus-basedStandards for the Selection of health status Measurement Instruments guidelines. Methods:A convenience sample of 1,129 nursing students attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 44 publications
0
32
0
7
Order By: Relevance
“…To assess the students’ ASE, we used the Academic Nurses’ Self‐Efficacy Scale (ANSEs) (Bulfone et al., 2020), which had previously been validated among nursing students. The dimensions of the scale included internal and external emotion management, autoregulatory behaviour and collegiality.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the students’ ASE, we used the Academic Nurses’ Self‐Efficacy Scale (ANSEs) (Bulfone et al., 2020), which had previously been validated among nursing students. The dimensions of the scale included internal and external emotion management, autoregulatory behaviour and collegiality.…”
Section: The Studymentioning
confidence: 99%
“…An exploratory factor analysis (EFA) revealed that the ANSE exhibited a good fit (CFI = 0.948), and the authors estimated a second‐order confirmatory factor that was good for every dimension (0.741 for external emotion management, 0.814 for internal emotion management, 0.561 for collegiality, and 0.578 for auto‐regulatory behaviour); the reliability coefficient was good (coefficient alpha = 0.84 for the entire scale). The standard error of measurement ( SEM ) was 0.69 and the smallest detectable difference (SDD) was 1.9 (26%) (Bulfone et al., 2020).…”
Section: The Studymentioning
confidence: 99%
“…What constitutes an at-risk student may be related to grades, attendance, participation, or the educator recognizing a pattern of behaviour (Tower et al, 2015). This early and proactive intervention may best be delivered as a form of feedback that supports careful self-appraisal and builds self-efficacy and study habits (Bulfone et al, 2019;Lammers, 2016). Awareness of nursing student self-efficacy can also be strengthened through a validated and reliable measure (Bulfone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This early and proactive intervention may best be delivered as a form of feedback that supports careful self-appraisal and builds self-efficacy and study habits (Bulfone et al, 2019;Lammers, 2016). Awareness of nursing student self-efficacy can also be strengthened through a validated and reliable measure (Bulfone et al, 2019). Instruments for understanding nursing student self-efficacy and other forms of feedback used to support successful study habits are avenues worth exploring in cohort and longitudinal analyses to learn more about student success from earlier failure.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, this structure refers to a person's beliefs about studying, doing research activities, asking questions in class, successful communication with the teacher, establishing intimate relationships with classmates, having good academic performance, and participating in class discussions (Zhen & et al, 2017). People with high academic self-efficacy usually have better academic performance, choose challenging goals, have lower anxiety and depression, are confident in their ability to succeed, and are more successful in academic activities (Bulfone & et al, 2020).…”
Section: Introductionmentioning
confidence: 99%